Comparison of the third year truants and non-truants in the Isabela High School - Bautista, Isidro (Isidro Lambenicio) 1944- (1988)
The purpose of this study was to find out if there are significant differences/similarities between third year non-truants in the Isabela High School as regards to mental ability, personality, self-concept, socio-economic status, academic achievement and their perceptions of their teachers' behavior. Some of the instruments used in the study were the IPAT Culture Fair Intelligence Test (CFIT) Scale 2, Form A and the Jr.-Sr. High School Personality Questionnaire. The findings of the study revealed that the mental ability, socio-economic status and academic achievement of the high school students have something to do in their being truant or non-truant. However, the personality profile, self-concept and perceptions of teachers' behavior had no effect in the boys being truant or non-truant.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: School attendance -- Philippines -- Isabela